Impulsive Noise Cancellation from ECG Signal using Adaptive Filters and their Comparison - Mihir Narayan Mohanty; Sarthak Panda (Institute of Advanced Engineering and Science, 2016)
Impulsive Noise is the sudden burst noise of short duration. Mostly it causes by electronic devices and electrosurgical noise in biomedical signals at the time of acquisition. In this work, Electrocardiograph (ECG) signal is considered and tried to remove impulsive noise from it. Impulsive noise in ECG signal is random type of noise. The objective of this work is to remove the noise using different adaptive algorithms and comparison is made among those algorithms. Initially the impulsive noise in sinusoidal signal is synthesized and tested for different algorithms like LMS, NLMS, RLS and SSRLS. Further those algorithms are modified in a new way to weight variation. The proposed novel approach is applied in the corrupted ECG signal to remove the noise. The effectiveness of the proposed approach is verified for ECG signal with impulsive noise as compared to the traditional approaches as well as previously proposed approaches. Also the performance of our approach is validated by SNR computation. Significant improvement in SNR is achieved after removal of noise.